PENGARUH GOOD CORPORATE GORVERNANCE, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI CORPORATE GORVERNANCE PRECEPTION INDEX (CGPI) PERIODE 2010-2012 - Lusi Extaliyus, 10.05.52.0129; Indarti, M.G. Kentris (Students Journal of Accounting and Banking, 2014)
This study is a study that examines the effect of Good Corporate Gorvernance, ownership structure, and firm size on financial performance in the Company registered in Corporate Gorvernance Preception Index (CGPI)Â year period 2010-2012. The sample used in this study is a company registered in Corporate Gorvernance Preception Index Â (CGPI) 2010-2012. The research method sample was purposive sampling, the number of samples obtained 60 Company. The analysis used is multiple linear regression and test the classical assumption of normality test, multicollinearity, autocorrelation test, test heterokedastisitas, the coefficient of determination test, F test, and the test statistic t. These results indicate that the variable of Good Corporate Gorvernance significant positive financial performance, managerial ownership significant positive effect on financial performance, Institutional Ownership is not significant positive effect on financial performance and firm size is not a significant positive effect on financial performance.Keywords: Good Corporate Gorvernance, ownership structure, company size and Return on Equity